Legendary Product

Let ( a p ) \left( \dfrac{a}{p} \right) denote the Legendre symbol .

If p = 2011 p = 2011 , find the value of a = 1 p 1 ( a p ) \ \displaystyle \prod_{a = 1} ^{p - 1} \ \left( \dfrac{a}{p} \right) .

None of these choices 0 -1 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Alexander Koran
Jan 17, 2017

So since Legendre symbol is multiplicative, we have (2010!/2011) and by Wilson's Theorem 2010! = -1 mod 2011, we have (-1/p) which is just -1.

Pranshu Gaba
Feb 13, 2016

For any odd prime p p , there exist p 1 p - 1 positive integers less than p p . Out of these p 1 p - 1 integers, exactly half of them, that is p 1 2 \frac{p - 1 }{2} are quadratic residues mod p p , and half of them are quadratic non-residues mod p p . This fact is proved in the Quadratic Residues wiki .

If 1 a p 1 1 \leq a \leq p - 1 , then the Legendre symbol denotes:

( a p ) = { 1 if a is a quadratic residue modulo p 1 if a is a quadratic non-residue modulo p \left( \frac{a}{p} \right) = \begin{cases} 1 & \text{ if } a \text{ is a quadratic residue modulo } p \\ - 1 & \text{ if } a \text{ is a quadratic non-residue modulo } p \\ \end{cases}

We saw that p 1 2 \frac{p - 1 }{2} quadratic residues and p 1 2 \frac{p - 1 }{2} quadratic non-residues in the interval 1 a p 1 1 \leq a \leq p -1 , therefore the product evaluates to

a = 1 p 1 ( a p ) = ( 1 ) ( p 1 ) / 2 × ( 1 ) ( p 1 ) / 2 \prod_{a = 1} ^{p - 1} \left( \frac{a}{p} \right) = (1)^{(p-1)/2} \times (-1)^{(p-1)/2}

In this problem, p = 2011 p = 2011 , therefore

a = 1 p 1 ( a p ) = ( 1 ) ( 2011 1 ) / 2 × ( 1 ) ( 2011 1 ) / 2 = 1 × ( 1 ) 1005 = 1 \begin{aligned} \prod_{a = 1} ^{p - 1} \left( \frac{a}{p} \right) & = (1)^{(2011-1)/2} \times (-1)^{(2011-1)/2} \\ & = 1 \times (-1) ^{1005} \\ & = \boxed{-1} & _\square \end{aligned}


In general, we can say that

a = 1 p 1 ( a p ) = { 1 if p 1 ( m o d 4 ) 1 if p 3 ( m o d 4 ) \prod_{a = 1} ^{p - 1} \left( \frac{a}{p} \right) = \begin{cases}1 & \text{ if } p \equiv 1 \pmod{4}\\ -1 & \text{ if } p \equiv 3 \pmod{4} \end{cases}

Bonus exercise: Try to prove this!

Moderator note:

Simple standard approach.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...